Clinical characteristics of COVID-19 patients with asthma in Wuhan, China: a retrospective cohort study. (1st February 2022) - Jin, Meng; Chen, Can; Huang, Jinyu; Zhang, Fengqin; Dong, Tianyi; Zhang, Ming; Yue, Huihui; Liu, Kui; Li, Guangcai; Hu, Ke; Zhang, Huilan
Abstract: Objective: Although it is reported that patients with coronavirus disease 2019 (COVID-19) disease who have comorbidities are at higher risk to suffer adverse clinical outcomes, there are inadequate evidence to clarify the association between COVID-19 and asthma. On this ground, this study aims to systematically analyze the clinical characteristics of COVID-19 patients with asthma. Methods: In this single-center, retrospective and observational cohort study, 21 COVID-19 patients with asthma and 100 non-asthma COVID-19 patients were statistically matched by propensity score based on age, sex and comorbidities. Meanwhile, a collection and comparison concerning demographic indicators, clinical and laboratory examinations, treatments and outcomes were conducted between two groups to specify their differences. Results: Statistically, the COVID-19 patients with asthma had a higher proportion of ICU admission (14.3% [3/21] vs. 2.1% [2/96] p  = 0.040) than those who do not have. On top this, a higher level of inflammatory responses, such as interleukin 6, interleukin 8, procalcitonin, leukocytes, neutrophils and CD4 + T cells was presented in asthma patients. Moreover, the increase of organ damage indices like D-dimer, lactate dehydrogenase and high-sensitivity cardiac troponin I, were more pronounced in COVID-19 patients with asthma. Conclusions: Exacerbated inflammatory responses and multiple organ damages were triggered in COVID-19 patients with asthma, which highlights more intensive surveillance and supportive treatment.